Emulsifying properties of quail egg white proteins in different vegetable oil emulsions - Lafetá Junior, José Antônio de Queiroz; Oliveira, Magno José de; Oliveira, Davi Rocha Bernardes de; Santos, Igor José Boggione; Saldaña, Marleny Doris Aranda; Coimbra, Jane Sélia dos Reis (Acta Scientiarum. Technology, 2020)
Emulsifying properties of oil in water emulsions using quail egg white protein (Coturnix coturnix japonica) as an emulsifying agent were investigated using the conductivity technique. Changes in emulsion conductivity were recorded during and after homogenization. The results were interpreted in terms of properties related to the emulsifying activity and emulsion stability. The effect of salt concentrations (NaCl) of 0.0, 0.29, 0.59, 1.17, 1.76, and 2.34% (w v-1) when mixed with egg white concentrations of 0.50, 1.00 and 1.50% (w v-1) were studied using corn and soybean vegetable oils. Globally, one observed that emulsifying activity and emulsion stability increase with the enhancement of salt concentration. However, the increase of the egg white concentration did not present a significant influence on emulsifying activity, causing an increment only in emulsion stability.